Flumazenil, a Benzodiazepine Receptor Anatagonist, in the Reversal of Conscious Sedation following Gastroscopy. A Placebo Controlled, Dose Finding Study. (1st December 1991) - Sutherland, Lloyd; Hershfield, Noel; Shaffer, Eldon; Price, Lorne; Dean, Deanne; Light, Margaret
Abstract : Tim double-blind, placebo controlled, study assessed the efficacy and safety of flumazenil, a benzodiazepine antagonist, in reversing diazepam-induced sedation in 60 patients undergoing endoscopy. Patients were randomly assigned to one of six treatment groups (placebo, 5, 10, 15, 20 or 25 μg/kg flumazenil). Patient psychomotor function was determined using four standard assessments – Trieger, digit substitution, track tracing and cancellation tests. Flumazenil was well tolerated by all patients. All doses of Flumazenil were superior to placebo in reversing sedation. No significant differences were detected between the various treatment groups. Forty-five minutes after the flumazenil infusion, there were no differences between flumazenil- and placebo-treated patients in psychomotor function. Flumazenil is a safe, effective medication which reverses diazepam-induced conscious sedation. For most patients 0.5 mg given intravenously will reverse sedation.